Exploring walnut (Juglans regia) in India: A comprehensive review on taxonomy, nutritional and medicinal properties - Neha Dhiman; Anshul Kumar; Komal Preet Kaur; Megha Ahir; Inder Dev (South African Journal of Botany, 2026)

Rational design and synthesis of theophylline-based hybrids as bacterial DHFR inhibitors: integrating molecular modelling and ADME prediction with biological validation - Jyoti; Garima; Nitish Kumar; Megha; Karanvir Singh; Rupali Rana; Aanchal Khanna; Irvanpreet Kaur; Sumanpreet Kaur; Preet Mohinder Singh Bedi (In Silico Pharmacology, 2026)

A comprehensive review of synthetic and semisynthetic xanthine oxidase inhibitors: identification of potential leads based on in-silico computed ADME characteristics - Rupali Rana; Anchal Sharma; Nitish Kumar; Aanchal Khanna; Jyoti; Muskan Dhir; Harmandeep Kaur Gulati; Jatinder Vir Singh; Preet Mohinder Singh Bedi (Molecular Diversity, 2025)

Effects of Mulching On Soil, Growth, and Biochemical Traits of Strawberry (Fragaria × ananassa) Under Protected Cultivation - Shailaja Punetha; Pooja Oli; Nidhi Joshi; Supriya Gupta; Prabhat Kumar; Manpreet Singh Preet; Vineet Kaswan; Rahul Dev; A. K. Goswami; Anjali Jingar; Daya Shankar Mishra; Prakashbhai Ravat; et al. (Applied Fruit Science, 2025)

Ferrocene-based compounds: promising anticancer and antimalarial agents in modern therapeutics - Anchal Sharma; Rupali Rana; Nitish Kumar; Harmandeep kaur gulati; Jyoti; Aanchal Khanna; Sofia Sharma; Pooja; Jatinder Vir Singh; Preet Mohinder Singh Bedi (Medicinal Chemistry Research, 2025)

Microbial inoculations and nitrogen application to decompose in situ rice residue ameliorate the microclimate and sustainability of Happy Seeder sown wheat in Indian Punjab - Rajbir Singh Khedwal; Jayesh Singh; Anu Kalia; K. B. Singh; Som Pal Singh; Achla Sharma; Aman Preet; Ishwar Singh; Joginder Kumar (Cereal Research Communications, 2025)

Antidiabetic potential of thiazolidinedione derivatives with efficient design, molecular docking, structural activity relationship, and biological activity: an update review (2021–2023) - Anchal Sharma; Nitish Kumar; Harmandeep Kaur Gulati; Rupali Rana; Jyoti; Aanchal Khanna; Muskan; Jatinder Vir Singh; Preet Mohinder Singh Bedi (Molecular Diversity, 2024)

Docetaxel-tethered di-Carboxylic Acid Derivatised Fullerenes: A Promising Drug Delivery Approach for Breast Cancer - Charu Misra; Jasleen Kaur; Manish Kumar; Lokesh Kaushik; Deepak Chitkara; Simran Preet; Muhammad Wahajuddin; Kaisar Raza (AAPS PharmSciTech, 2024)

Sustainable solutions for food security: Evaluating pre-treatment technologies in the growing fruits and vegetables industry of India - Aroma Joshi; Arun Kumar Gupta; Mansi; Shivani Semwal; Nandini Deoli; Muzamil Ahmad Rather; Bindu Naik; Vijay Kumar; Avinash Kumar Jha; Sarvesh Rustagi; Manpreet Singh Preet (Sustainable Chemistry and Pharmacy, 2024)

Morpho-physiological analysis of salinity tolerance in sugarcane genotypes - Kumar Preet; Pooja Dhansu; Nirmala Sehrawat; Ravinder Kumar; C. Appunu; Krishnapriya Vengavasi; Raja Arunkumar; Rohit Rana; Surender Kumar; Vikas Joon (Plant Physiology Reports, 2024)

Utilizing marine algal metabolites to fight neurodegenerative diseases - Bindu Naik; Shruti Richa; Shivangi Bharadwaj; Sadhna Mishra; Vijay Kumar; Vivek Kumar; Per Erik Joakim Saris; Arun Kumar Gupta; Ritesh Mishra; Uttam Gupta; Sarvesh Rustagi; Manpreet Singh Preet (Frontiers in Marine Science, 2024)
Marine algae are thought to be a source of various metabolites that have a wide range of positive effects on human health. The pharmacological properties of algal metabolites, including their antioxidant, anti-inflammatory, cholesterol homeostasis, protein clearance, and anti-amyloidergic effects, lend credence to their protective efficacy against oxidative stress, neuroinflammation, mitochondrial dysfunction, and impaired proteostasis, all of which are involved in the pathophysiology of neurodegenerative disorders. There are currently no clinical trials on the effects of marine algae on neuroinflammation; however, considering the significant biological activities that have been established by in vitro and animal research, we expect that there will be clinical trials on this topic in the not-too-distant future. The most recent and important findings on the potentially neuroprotective effects of the anti-inflammatory properties of marine algae were chosen for this study. Next, we conducted a literature review on the neuroprotective potential of algal compounds, along with the underlying pharmacological mechanism, and finally, we evaluated recent advances in therapeutics.

Household cooking fuel and gallbladder cancer risk: a multi-centre case–control study in India - Krithiga Shridhar; Manigreeva Krishnatreya; Ranjit Kumar; Dimple Kondal; Mouchumee Bhattacharyya; Banti Kalita; Prakriti Snehil; Amulya K. Singh; Amal Chandra Kataki; Ashok Ghosh; D.Prabhakaran; Poornima Prabhakaran; et al. (Cancer Causes & Control, 2024)

Chagas parasite classification in blood sample images using different machine learning architectures - Lavdie Rada; Preet Kumar; Anabel Martin-Gonzalez; Carlos Brito-Loeza (Medical & Biological Engineering & Computing, 2024)

Anticonvulsant potential of Grewia tiliaefolia in pentylenetetrazole induced epilepsy: insights from in vivo and in silico studies - Ankita Rajput; Palvi Sharma; Nitish Kumar; Hasandeep Singh; Tanveer Singh; Sharabjit Singh; Preet Mohinder Singh Bedi; Balbir Singh; Saroj Arora; Sarabjit Kaur (Metabolic Brain Disease, 2023)

A multi-scale algorithm for the NISAR mission high-resolution soil moisture product - Preet Lal; Gurjeet Singh; Narendra N. Das; Dara Entekhabi; Rowena Lohman; Andreas Colliander; Dharmendra Kumar Pandey; R.K. Setia (Remote Sensing of Environment, 2023)

Shikonin derivatives as potent xanthine oxidase inhibitors: in-vitro study - Nitish Kumar; Ankita Rajput; Harmandeep Kaur; Anchal Sharma; Kavita Bhagat; Jatinder Vir Singh; Saroj Arora; Preet Mohinder Singh Bedi (Natural Product Research, 2023)

Brassica juncea leaf cuticle contains xylose and mannose (xylomannan) which inhibit ice recrystallization on the leaf surface - Kailash Yadav; Meenakshi Arya; Satya Prakash; Bhavana Sharma Jha; Preet Manchanda; Abhishek Kumar; Renu Deswal (Planta, 2023)

Quinoline derivatives volunteering against antimicrobial resistance: rational approaches, design strategies, structure activity relationship and mechanistic insights - Nitish Kumar; Aanchal Khanna; Komalpreet Kaur; Harmandeep Kaur; Anchal Sharma; Preet Mohinder Singh Bedi (Molecular Diversity, 2023)

Discovery of potent inhibitors for M pro enzyme of SARS-COV2 by multi-stage in-silico screening of Alkannin/shikonin - Nitish Kumar; Jatinder Vir Singh; Kavita Bhagat; Harmandeep Kaur Gulati; Anchal Sharma; Archana Rani; Amit Duggal; Puja Gulati; Harbinder Singh; Preet Mohinder Singh Bedi; Sarabjit Kaur (Natural Product Research, 2022)

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Influence of Super Cyclone “Amphan” in the Indian Subcontinent amid COVID-19 Pandemic - Shubham Kumar; Preet Lal; Amit Kumar (Remote Sensing in Earth Systems Sciences, 2021)

Most recent strategies targeting estrogen receptor alpha for the treatment of breast cancer - Nitish Kumar; Harmandeep Kaur Gulati; Aakriti Sharma; Shilpa Heer; Anupmjot Kaur Jassal; Lovenish Arora; Simranpreet Kaur; Atamjit Singh; Kavita Bhagat; Arshmeet Kaur; Harbinder Singh; Jatinder Vir Singh; et al. (Molecular Diversity, 2021)

Rational approaches for the design of various GABA modulators and their clinical progression - Kavita Bhagat; Jatinder V. Singh; Piyusha P. Pagare; Nitish Kumar; Anchal Sharma; Gurinder Kaur; Nihar Kinarivala; Srinivasa Gandu; Harbinder Singh; Sahil Sharma; Preet Mohinder S. Bedi (Molecular Diversity, 2021)

Google Earth Engine for concurrent flood monitoring in the lower basin of Indo-Gangetic-Brahmaputra plains - Preet Lal; Aniket Prakash; Amit Kumar (Natural Hazards, 2020)

Design, synthesis and biological evaluation of novel indolinedione–coumarin hybrids as xanthine oxidase inhibitors - Harmandeep Kaur Gulati; Kavita Bhagat; Atamjit Singh; Nitish Kumar; Arshmeet Kaur; Akriti Sharma; Shilpa Heer; Harbinder Singh; Jatinder Vir Singh; Preet Mohinder S. Bedi (Medicinal Chemistry Research, 2020)

Turbulence of tropical cyclone ‘Fani’ in the Bay of Bengal and Indian subcontinent - Shubham Kumar; Preet Lal; Amit Kumar (Natural Hazards, 2020)

Root exudates ameliorate cadmium tolerance in plants: A review - Aditi Shreeya Bali; Gagan Preet Singh Sidhu; Vinod Kumar (Environmental Chemistry Letters, 2020)

Photosynthetic Response of Plants Under Different Abiotic Stresses: A Review - Anket Sharma; Vinod Kumar; Babar Shahzad; M. Ramakrishnan; Gagan Preet Singh Sidhu; Aditi Shreeya Bali; Neha Handa; Dhriti Kapoor; Poonam Yadav; Kanika Khanna; Palak Bakshi; Abdul Rehman; et al. (Journal of Plant Growth Regulation, 2020)

Retrospect and prospects of secondary agriculture and bioprocessing - Sudesh Kumar Yadav; Baljinder Singh Kauldhar; Pankaj Preet Sandhu; Karnika Thakur; Sucheta; T. R. Sharma (Journal of Plant Biochemistry and Biotechnology, 2020)

Microwave-assisted synthesis of 11-substituted-3,3-dimethyl-2,3,4,5,10,11-hexahydrodibenzo[b,e][1,4]diazepin-1-one derivatives catalysed by silica supported fluoroboric acid as potent antioxidant and anxiolytic agents - Kavita Bhagat; Atamjit Singh; Suruchi Dhiman; Jatinder Vir Singh; Ramandeep Kaur; Gurinder Kaur; Harmandeep Kaur Gulati; Palwinder Singh; Raman Kumar; Rajan Salwan; Kajal Bhagat; Harbinder Singh; et al. (Medicinal Chemistry Research, 2019)

Genomic alterations associated with HER2+ breast cancer risk and clinical outcome in response to trastuzumab - Heena Singla; Raman Preet Kaur; Gowhar Shafi; Rajesh Vashistha; Raja Paramjeet Singh Banipal; Vinod Kumar; Anjana Munshi (Molecular Biology Reports, 2019)

Association of CYP2C19*2 and ALDH1A1*1/*2 variants with disease outcome in breast cancer patients: results of a global screening array - Sourav Kalra; Raman Preet Kaur; Abhilash Ludhiadch; Gowhar Shafi; Rajesh Vashista; Raj Kumar; Anjana Munshi (European Journal of Clinical Pharmacology, 2018)

Management of Staphylococcus Mediated Systemic Infection by Enhancing the Resurging Activity of Co-trimoxazole in Presence of Cryptdin-2 - Amrita Kaur; Shiv Kumar Chabba; Ujjwal Jit Kaur; Arashdeep Kaur; Simran Preet; Praveen Rishi (Indian Journal of Microbiology, 2017)

Alterations in photosynthetic pigments, protein, and carbohydrate metabolism in a wild plant Coronopus didymus L. (Brassicaceae) under lead stress - Gagan Preet Singh Sidhu; Harminder Pal Singh; Daizy R. Batish; Ravinder Kumar Kohli (Acta Physiologiae Plantarum, 2017)

Screening of a library of 4-aryl/heteroaryl-4H-fused pyrans for xanthine oxidase inhibition: synthesis, biological evaluation and docking studies - Ramandeep Kaur; Fatima Naaz; Sahil Sharma; Samir Mehndiratta; Manish Kumar Gupta; Preet Mohinder Singh Bedi; Kunal Nepali (Medicinal Chemistry Research, 2015)

Celtisanin, a novel sulphonated phenolic from Celtis australis L. fruits - Ruchi Badoni; Deepak Kumar Semwal; Usha Rawat; Gur Jas Preet Singh (Natural Product Research, 2010)

Immunogenicity of cholera toxin B epitope inserted in Salmonella flagellin expressed on bacteria and administered as DNA vaccine - Neeraj Chauhan; Ravindra Kumar; Jitendra Badhai; Anju Preet; Pramod Kumar Yadava (Molecular and Cellular Biochemistry, 2005)